Pengaruh Pemasaran Digital dan Pemasaran Konvensional terhadap Loyalitas Konsumen melalui Kepuasan Konsumen di Timor-Leste - Bonifacio José Tilman; Miswanto Miswanto; Frasto Biyanto; Baldric Siregar (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to analyze the effect of digital and conventional marketing strategies on customer loyalty through customer satisfaction as a mediating variable using the Stimulus–Organism–Response (SOR) approach in the private sector in Timor-Leste. A quantitative approach with a cross-sectional survey design was employed. Data were collected from 200 respondents who had transactions with private companies. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that both digital and conventional marketing have a positive and significant effect on customer satisfaction, and customer satisfaction significantly influences customer loyalty. In addition, customer satisfaction fully mediates the relationship between marketing strategies and customer loyalty. These findings indicate that loyalty is formed through satisfaction as a psychological response to marketing stimuli.